Quantitative determination of gabapentin by spectrophotometric method - Budnik, D. K.; Miedviedieva, K. P.; Мєдвєдєва, Катерина Павлівна (Запорізький державний медичний університет, 2021)
Gabapentin is an antiepileptic product for oral administration. Epilepsy is considered one of the most common chronic neurological diseases among humans. About 50 million people worldwide live with epilepsy and 2.4 million new cases are reported each year. There are about 100,000 people having epilepsy in Ukraine. Epilepsy is a chronic disorder of brain activity that is characterized by repeated attacks. The structure of gabapentin is similar to the GABA (gamma-aminobutyric acid). That is why the urgent aim for pharmaceutical analysis is developing of high precision, valid, accessible and express methods of quantification.
Keywords: тези